2022
DOI: 10.1097/inf.0000000000003639
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Characteristics, and Outcomes of Clinically Undetected Bacteremia in Children Discharged Home From the Emergency Department

Abstract: Background: Despite a recent decline in the rates of invasive infections, bacteremia in young children remains a significant challenge. We aimed to describe patient characteristics, microbial etiology, and outcomes of bacteremic, well-appearing children 3–36 months of age who were discharged home from the pediatric emergency department (PED) on their index visit. Methods: A retrospective cohort study in the PED of a tertiary children’s hospital from 1 June 2015 until 30 June 2021. We included all well appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Our results are similar to small single-center studies from the past 10 years that have reported a wider range of bacteremia (0.3%-4.2%, with a weighted average of 1.9%), limited by their smaller sample sizes . The incidence of bacteremia in SCD has decreased over the past 30 years in conjunction with the introduction of prophylactic measures, disease-modifying medications, and vaccine development, but it still occurs and is higher than the risk of undetected bacteremia in febrile young children (age 3-36 months) without SCD who present to the ED . Our results focus on the risk of bacteremia among children with SCD and fever who have already arrived in a pediatric ED.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results are similar to small single-center studies from the past 10 years that have reported a wider range of bacteremia (0.3%-4.2%, with a weighted average of 1.9%), limited by their smaller sample sizes . The incidence of bacteremia in SCD has decreased over the past 30 years in conjunction with the introduction of prophylactic measures, disease-modifying medications, and vaccine development, but it still occurs and is higher than the risk of undetected bacteremia in febrile young children (age 3-36 months) without SCD who present to the ED . Our results focus on the risk of bacteremia among children with SCD and fever who have already arrived in a pediatric ED.…”
Section: Discussionsupporting
confidence: 81%
“… 12 , 18 The incidence of bacteremia in SCD has decreased over the past 30 years in conjunction with the introduction of prophylactic measures, disease-modifying medications, and vaccine development, 4 , 5 , 10 , 19 but it still occurs and is higher than the risk of undetected bacteremia in febrile young children (age 3-36 months) without SCD who present to the ED. 20 Our results focus on the risk of bacteremia among children with SCD and fever who have already arrived in a pediatric ED. The relatively low risk of bacteremia and the positive outcomes achieved even for children who were diagnosed with bacteremia who were initially discharged from the ED and later readmitted, may be useful for discussion among ED and acute care clinicians about the appropriate workup, treatment, and disposition of children with SCD and fever and whether a more targeted deployment of resources is feasible.…”
Section: Discussionmentioning
confidence: 99%